A taste for victory - Terrell, Brandon, 1978-; e (North Mankato, Minnesota : Stone Arch Books, a Capstone imprint, 2021)
Hank Watson loves playing basketball and helping his team win big games. But he has another passion too--cooking! When Hank has an opportunity to meet celebrity chef Brenton Spooner, he jumps at the chance. But while practicing a difficult dish, he accidentally burns his hand. The injury affects his performance both on the court and in the kitchen.
3.5
3-6
GN560L
Keywords: Basketball -- Comic books, strips, etc. -- Juvenile fiction; Cooking -- Comic books, strips, etc. -- Juvenile fiction; Basketball -- Fiction; Cooking -- Fiction; Cartoons and comics; Sports comics; Graphic novels; Comics (Graphic works)